2016
DOI: 10.1016/j.cej.2015.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of g-C3N4 by hydrazine: Simple way for noble-metal free hydrogen evolution catalysts

Abstract: The graphitic carbon nitride (g-C 3 N 4 ) usually is thought to be an inert material and it's difficult to have the surface terminated NH 2 groups functionalized. By modifying the g-C 3 N 4 surface with hydrazine, the diazanyl group was successfully introduced onto the g-C 3 N 4 surface, which allows the introduction with many other function groups. Here we illustrated that by reaction of surface hydrazine group modified g-C 3 N 4 with CS 2 under basic condition, a water electrolysis active group C(=S)SNi can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…In relation to the ATR-FTIR spectra of MMMs doped with oxygen plasma and hydrazine treated g-C 3 N 4 , also depicted in Figure 3, it is worth noting that no bands associated with the N–OH or –NHNH 2 groups of g-C 3 N 4 (which would result from those treatments) were observed. This may be due to low dopant doses, and would be in agreement with the findings of Chen et al [35], who reported no remarkable differences between pristine g-C 3 N 4 and g-C 3 N 4 -NHNH 2 . On the other hand, the band at 1606 cm −1 , present in the pristine matrix, was found to disappear upon doping in both cases.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In relation to the ATR-FTIR spectra of MMMs doped with oxygen plasma and hydrazine treated g-C 3 N 4 , also depicted in Figure 3, it is worth noting that no bands associated with the N–OH or –NHNH 2 groups of g-C 3 N 4 (which would result from those treatments) were observed. This may be due to low dopant doses, and would be in agreement with the findings of Chen et al [35], who reported no remarkable differences between pristine g-C 3 N 4 and g-C 3 N 4 -NHNH 2 . On the other hand, the band at 1606 cm −1 , present in the pristine matrix, was found to disappear upon doping in both cases.…”
Section: Resultssupporting
confidence: 93%
“…In the later approach, diazanyl group modified g-C 3 N 4 -NHNH 2 (Figure 1c) was obtained according to the procedure described by Chen et al [35]: 1 g of as-synthesized g-C 3 N 4 was mixed with 20 mL water and 4 mL hydrazine hydrate, followed by stirring at 80 °C for 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…As seen in Fig. 3C, the ve peaks at 2.2, 5.1, 8.7, 11.5 and 13.5 ppm in the 1 H NMR spectra were assigned to the protons in aliphatic groups, residual water, NH x groups, the hydrogen bonds in acid groups (such as carboxylic acid and phosphoric acid) and g-C 3 N 4 framework, [33][34][35] respectively. Thus, the intensication of the 8.7 or 11.5 ppm peak can be regarded as evidence for the protonation of g-C 3 N 4 nanosheets.…”
Section: Structure Characterizationmentioning
confidence: 91%
“…[4,7] Most importantly,i th as ab and gap of % 2.7 eV suitable for photocatalytic hydrogen production. [8][9][10] However,t he pristine g-C 3 N 4 was affectedb yt he rapid recombination rate of photo-generated carriers (e À and h + ), which greatly impeded the photocatalytic performance. In order to furtheri mprove the photocatalytic activity of g-C 3 N 4 ,s ome research progress have been done, for example (i)microstructure modification; [11] (ii)forming ah eterojunction with other semiconductors; [12] (iii) copolymerization with organic monomers; [13] (iv) co-catalyst modification.…”
Section: Introductionmentioning
confidence: 99%